Bayesian estimation of the relative deviations between activities in the radionuclide standardization - Fabio Ludolf Cacais; José Ubiratan Delgado; Victor Manuel Loayza; Johnny Almeida Rangel (Brazilian Journal of Radiation Sciences, 2019)
The dissemination of the activity is performed from radionuclide sources prepared in a sequence of dilutions and weighing methods. In this process, the activity of the source can be estimated statistically from the deposited mass and the activity concentration of the master solution. After preparation, the activity is obtained from absolute or relative measurement methods. However, the methods of activity determinations used may not fulfill the necessary independence of the conventional statistical approach due to the presence of possible correlations between activities that arise with the use of the same standardized sources or with the same method of quantity measurements. In this paper, Bayesian estimates for the relative deviation of activities and their uncertainty were obtained in order to evaluate the performance of the main sources’ preparation method. The estimate result (0.55 ± 0.27) % for a data set of radionuclide standardization performed between 2017 and 2018 at LNMRI, although close to zero, shows one should investigate possible effects affecting the preparation and measurement of the sources. This Bayesian estimate was validated by monte carlo simulation method.